The Effect of Footwork Trainner on Agility and Vo2max in Badminton Athletes - Bimo, Satrio; Permana, Dhias Fajar Widya (Universitas Majalengka, 2024)
This research aims to determine: (1) the effect of footwork trainers on the agility of badminton athletes in the 10-12 year age group at PB Jati Wetan Kudus. (2) the effect of footwork trainer on VO2max of badminton athletes in the 10-12 year age group at PB Jati Wetan Kudus. The research uses an experimental method with a